Left ventricular hypertrophy, diastolic dysfunction and right ventricular load predict outcome in moderate aortic stenosis - Stöbe, Stephan; Kandels, Joscha; Metze, Michael; Tayal, Bhupendar; Laufs, Ulrich; Hagendorff, Andreas (Frontiers in Cardiovascular Medicine, 2023)
Aims Predictors of progression of moderate aortic valve stenosis (AS) are incompletely understood. The objective of this study was to evaluate the prognostic value of left ventricular hypertrophy (LVH), diastolic dysfunction, and right ventricular (RV) load in moderate AS. Methods and results Moderate AS was defined by aortic valve area (AVA), peak transvalvular velocity (Vmax) or mean pressure gradient (PGmean). A total of 131 Patients were divided into two groups according to the number of pathophysiological changes (LVH, diastolic dysfunction with increased LV filling pressures and/or RV load): <2 (group 1); ≥2 (group 2). The primary outcome was survival without aortic valve replacement (AVR). After follow-up of 30 months, the reduction of AVA (–0.06 ± 0.16 vs. –0.24 ± 0.19 cm2, P < 0.001), the increase of PGmean (2.89 ± 6.35 vs 6.29 ± 7.13 mmHg, P < 0.001) and the decrease of the global longitudinal strain (0.8 ± 2.56 vs. 1.57 ± 3.42%, P < 0.001) from baseline to follow-up were significantly more pronounced in group 2. Survival without AVR was 82% (group 1) and 56% (group 2) [HR 3.94 (1.74–8.94), P < 0.001]. Survival without AVR or progression of AS was 77% (group 1) and 46% (group 2) [HR 3.80 (1.84–7.86), P < 0.001]. The presence of ≥2 pathophysiological changes predicted outcome whereas age, comorbidities, LDL-cholesterol did not. Conclusion The presence of ≥2 pathophysiological changes is a strong predictor of outcome in moderate AS and may be useful for risk stratification, particularly for scheduling follow-up time intervals and deciding the timing of AVR.